Dancing in the light - MacLaine, Shirley, 1934- (Toronto ; New York : Bantam Books, 1985)
The Oscar award winning actress explores her choices, beliefs, and conflicts since her fiftieth birthday
Keywords: MacLaine, Shirley, -- 1934-; Entertainers -- United States -- Biography; Spiritualists -- United States -- Biography